Moderate exercise combined with dietary vitamins C and E counteracts oxidative stress in the kidney and lens of streptozotocin-induced diabetic rat - Kutlu, M; Naziroglu, M; Simsek, H; Yilmaz, T; Kükner, AA (Imr Press, 2005)
Oxidative stress has a key role in the pathogenesis of diabetes-induced cataract formation and nephropathy. Daily moderate exercise and vitamins C and E (VCE) supplementation can be beneficial to diabetes due to reducing blood glucose and free radical production. The aim of this study was to analyze the effect of moderate exercise with vitamin VCE on lipid peroxidation (LP) and antioxidative systems in the kidneys and lens of streptozotocin-induced diabetic rats. Forty female Wistar rats were used. They were randomly divided into four groups. The first and second groups were used as control and diabetic groups. The third group was the diabetic-exercise group. VCE-supplemented feed was given to diabetic-exercise rats constituting the fourth group. Animals in the exercised groups were moderately exercised daily on a treadmill for three weeks (five days a week). Diabetes was induced on day zero of exercise. Body weights in the four groups were recorded weekly. Lens and kidney samples were taken from all animals on day 20. Glutathione peroxidase (GSH-Px), reduced glutathion (GSH), vitamin E, and beta-carotene levels in kidney and lens, albumin in plasma, and body weight were significantly lower in the diabetic group than in the control groupo, whereas there was a significant increase in LP of kidney and lens as well as plasma glucose, urea, and creatinine levels in the diabetic group. The decrease in antioxidant enzymes, vitamins, and albumin and the increase in LP and glucose levels in diabetic rats were significantly improved with exercise and VCE supplementation. In the diabetic animals, the decreased beta-carotene and vitamins A levels in kidney did not improve through exercise only, although their levels were increased by exercise plus VCE supplementation. In conclusion, these data demonstrate that lipid peroxidation increases in the lens and kidney of diabetic animals and this could be due to decreases in antioxidant vitamins and enzymes. However, dietary VCE with moderate exercise may strengthen the antioxidant defense system through the reduction of ROS and blood glucose levels. The VCE supplementations with exercise may play a role in preventing the development of diabetic nephropathy and cataract formation in diabetic animals.
Keywords: oxidative stress; diabetes; exercise; lens and kidney; vitamins C and E